Developing a digital co-creation assessment methodology - Raluca Vasilache; Madalin Darie (Contemporary Economics, 2018)
Digitally enhanced public open spaces are ideal environments for the social innovations to emerge due to the involvement of the entire community and ICT (Information and Communication Tools) in knowledge creation and aggregation. This research paper presents an early-stage methodological digital co-creation assessment framework that considers a variety of aspects to transform public open places into co-created spaces: socio-cultural contexts, multi-stakeholder perspective, diversity in needs, incentives for participation of different groups and cooperation capabilities. The framework incorporates these aspects and proposes a suitable community-wide co-creation model employing the creative, innovative and cooperative applications of ICT. The assessment methodology is developed using a pragmatic mixed-method research design where the theoretical framework summarizes current research progress on the topic and the expert interviews allow to condense the complex and multi-dimensional realities for decision-makers seeking social innovations in the public spaces. The methodological assessment framework presented in this paper strengthens the scientific evidence regarding the potential of co-creation in developing social innovations and provides a managerial framework for developing co-creative initiatives.
Keywords: Q55; L38; O35; 330; Co-Creation; Public Spaces; ICT; Social Innovation